Performance analysis of the network communication based on AMR speech coding by using NS - JIA Long-tao; BAO Chang-chun (Tongxin xuebao)
Most of the VoIP systems were based on the speech codec with a fixed rate,which maked packet-loss serious,especially for continuous packet-loss.The degradation for the speech quality would be caused by the kind of packet-loss.A network communication system for preventing packet-loss was given.The performance of the system was analyzed by using advanced NS.The simulation results show that the proposed system outperforms traditional IP system over the packet-loss,average delay and subjective listening quality.